Unmet Menstrual Needs Among Bangladeshi Female University Students: A Nationwide Cross‐Sectional Study Using the MPNS‐36 Scale - Md. Mahadi Hassan; Noushin Nohor; Ikram Hossen; Sahara Yasmin; Tasnim B. K. Chowdhury; Jayma Jannat Juma; Marjia Khan Trisha; Nusrat Jahan; Kamrun Nahar Momo; Nahida Bintee Mostofa; Most. Mariam Jamila; Anika Bushra Boitchi (Health Science Reports)
ABSTRACT Background Attention to the menstrual needs of women is a crucial step toward finding and addressing the barriers to their menstrual health and hygiene management. The menstrual needs of female university students in Bangladesh are heavily understudied and require scrutiny to find the current state of the situation. Their menstrual needs assessment can provide insights that can be used to initiate steps for improving their menstrual health and hygiene practices. Purpose This study was aimed at evaluating the current status of menstrual needs satisfaction and factors that undermine it among female university students in Bangladesh. Methods A nationwide cross‐sectional study was conducted from January 2024 to February 2024, across eight universities in Bangladesh using a questionnaire containing socio‐demographics and a previously developed and validated MPNS‐36 scale. The eight divisions in Bangladesh and the universities within those divisions were considered clusters in the sampling procedure. A total of 625 participants were recruited using a multistage cluster random sampling technique. We used descriptive statistics to present socio‐demographic and distribution statistics, where categorical variables were presented as n (%) and numeric variables as means ± standard deviations. The multivariate linear regression was used to identify potential factors associated with unmet menstrual needs among female university students. Results According to the MPNS‐36 score, 99% of female university students reported unmet menstruation needs. The mean needs score of the participants was 1.61 ± 0.50, indicating the presence of unmet menstrual needs. In the case of specific menstrual needs, the mean score for materials and home environment needs, transport and university environment needs, material reliability concern, change and disposal insecurity, reuse needs, and reuse insecurity was 1.93 ± 0.72, 1.57 ± 0.71, 1.50 ± 0.78, 1.24 ± 0.67, 1.79 ± 0.92, and 1.31 ± 0.90 respectively. Factors such as religion (p = 0.005), educational level (p = 0.036), and parental education (p = 0.008) were found to be significantly associated with unmet menstrual needs. Conclusion We found that a large number of university students are not able to fulfill their menstrual hygiene needs. This indicates a requirement for improved facilities and a menstrual management environment for female university students to safeguard their reproductive health.